HUBUNGAN ADIPONEKTIN ASI DENGAN BERAT BADAN BAYI USIA 1-3 BULAN - Peny Ariani; Delmi Sulastri; Gusti Revilla (JURNAL KEBIDANAN KESTRA (JKK), 2018)
Adiponectin is a hormone that plays a role in the body’s metabolic system. Adiponectin is found in breast milk and has an important role on the growth of babies and are associated with baby weight gain. The aim of this study was to fine the relationship between adiponection level of breast milk and the weight of 1-3 month old babies. The study was designed to be analytic cross-sectional observational upon 32 pospartum mothers who breastfeed exclusively in the working territory of Andalas, Alai, and Ambacang Community Health Center, Padang from March until November 2015. The sample was selected by consecutive sampling. Examination of adiponectin level in breast milk was conducted in Biomedical Laboratory of Faculty of Medicine of Andalas University by using ELISA method. Data normality was tested by Saphiro-Wilk, paired t test for mean difference and Pearson correlation test to assess the the correlation between adiponectin level in breast milk and baby weight by using SPSS version 16.0. The mean of adiponectin level in breast milk at 1 and 3 months postpartum was 33,32±13,50 ng/mL and 39,88±13,48 ng/mL (p<0,05). There was significant negative correlation between adiponectin level in breast milk and the weight of 0-1 month old babies(r=-0,437; p<0,05). There was weak negative correlation between adiponectin level in breast milk and the weight of 1 and 3 month old babies(r=-0,228 ; p>0,05) and (r=-0,177 ; p>0,05). In conclusion, adiponectin level in breast milk in the first month postpartum is lower than that in the third month postpartum. Adiponectin level in breast milk was negatively correlated with the increase of baby weight gain.